(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to analyze the chemical parameters and major anionic contents of water from Taltola and Mullahbari Pond at Santosh, Tangail during the months from January to March 2014. Chemical parameters such as pH, EC, DO, TDS, BOD and Alkalinity of all water samples were ranged from 7.56 to 7.78, 239.7 to 342 ?S/cm, 4.3 to 5.7 mg/L, 123.7 to 175 mg/L, 2.1 to 2.63 mg/L and 87 to 154 ppm, respectively. On the other hand, the anions such as F-, Cl-, NO2-, NO3-, SO4– were ranged from 0.221 to 3.8, 16 to 24, 2.5 to 3.8, 0.96 to 1.67 and 1.99 to 17.93 mg/L, respectively. In case of Br- the anionic value of water sample was not detectable. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22213 J. Environ. Sci. & Natural Resources, 7(2): 89-92 2014